Mobility and Progressive Taxation - Marcus Roller; Kurt Schmidheiny (European Regional Science Association (ERSA), 2014)
In fiscally centralised countries with a unique country-wide income tax schedule, it is straightforward to quantify the degree of progressivity. In fiscally decentralised countries with varying local tax schedules, however, this is not the case. In these countries, the effective tax progressivity depends on the distribution of taxpayers across local jurisdiction as well as on local income distributions. The latter might differ systematically because high income households can partly or fully avoid high tax rates by sorting into low tax locations. This paper develops an empirical approach in order to quantify the effective tax progressivity in a fiscally highly decentralised country - Switzerland - taking the relative size of jurisdictions and the actually observed income sorting into account. Exploiting data on the universe of Swiss taxpayers, we find that rich households face significantly lower tax rates and lower progressivity than in the benchmark case that does not take the income sorting into account. The results are stronger for singles than for families indicating that singles are more sensitive to tax differentials than families. Furthermore, we find suggestive evidence that due to this income sorting the Swiss income tax system is not only less progressive but even regressive for single households with very high incomes.
Keywords: H71; H73; R23; 330; Progressive Taxation; Fiscal Decentralisation; Income Segregation